A comparative analysis of three marine governance systems for implementing the Convention on Biological Diversity (CBD). (April 2016) - Jones, Estelle Victoria; Gray, Tim; Macintosh, Donald; Stead, Selina
Abstract: Successful implementation of the Convention on Biological Diversity (CBD) requires critical reflection on governance structures especially in the biodiverse tropics where institutional capacity is weak and fragmented. This paper explores three modes of marine governance in Thailand and discusses the challenges each faces when delivering conservation and sustainable development objectives. Focusing on Marine Protected Areas (MPA), the dominant management approaches to biodiversity conservation, centralised, decentralised and shared governance, are scrutinised through a review of the literature and 24 key informant interviews with leading Thai academics, national and regional government officers and NGOs. We find both the centralised, state-managed MPA system and the decentralised, community-based MPA system to have severe limitations, for different reasons, in protecting biodiversity, whereas shared governance, despite being less common, is the best intermediate mode. Shared governance is the most viable option available in Thailand for working towards key CBD targets because: (1) local participation can legitimise much of the relationship with the centralised system and can help embed a decentralised system in natural resources management; (2) the centralised system will still remain in ultimate control, which, whilst not favoured by those who want decentralisation, will satisfy powerful elites, and offer more opportunity to empower local people to take responsibility for conservation targets; and (3) the capacity of both local and national stakeholders can be built to deal with the complexity of the marine environment. Highlights: Explores how modes of governance deliver conservation and sustainable development. State-managed and community-based MPA systems have severe limitations. Shared governance is the most viable option for working towards key CBD targets. Local participation legitimises relationships whilst centralisation retains control. Capacity can be built to deal with the complexity of the marine environment.